2023
DOI: 10.3389/fsurg.2022.1086735
|View full text |Cite
|
Sign up to set email alerts
|

Application of femoral nerve block combined with modified swelling anesthesia in high ligation and stripping of great saphenous vein

Abstract: BackgroundTo analyze and explore the clinical efficacy of ultrasound guided femoral nerve block combined with modified swelling anesthetic solution in high ligation and stripping of the great saphenous vein.Methods90 patients with varicose great saphenous vein of lower limbs undergoing high ligation and stripping of great saphenous vein were randomly divided into group A (femoral nerve block combined with modified swelling anesthesia), group B (simple swelling anesthesia) and group C (epidural anesthesia), wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…However, we found that multiple puncture injections into the skin would cause pain and discomfort to the patients, especially in the process of PS; the number of remedial injections and the amount of TAS were significant, significantly increasing pain, reducing comfort, and even affecting the surgical effect. It has been reported in the literature 8 , 9 that the application of ultrasound-guided femoral nerve block (FNB) combined with tumescent anesthesia (TA) in lower extremity varicose surgery has a better anesthetic effect than TA alone. However, applying ultrasound-guided FNB with TA in EVRA combined with PS is rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, we found that multiple puncture injections into the skin would cause pain and discomfort to the patients, especially in the process of PS; the number of remedial injections and the amount of TAS were significant, significantly increasing pain, reducing comfort, and even affecting the surgical effect. It has been reported in the literature 8 , 9 that the application of ultrasound-guided femoral nerve block (FNB) combined with tumescent anesthesia (TA) in lower extremity varicose surgery has a better anesthetic effect than TA alone. However, applying ultrasound-guided FNB with TA in EVRA combined with PS is rarely reported.…”
Section: Introductionmentioning
confidence: 99%